Physiological adaptations in small-side games combined with speed-endurance training: analyzing heart rate and rate of perceived exertion - Muhammad Bagus Firzam Bharlaman; I Dewa Made Aryananda Wijaya Kusuma; Nining Widyah Kusnanik; David Agus Prianto; Adi Pranoto (IP Iermakov S.S., 2024)
Background and Study Aim. Monitoring physiological responses during training is crucial for understanding how athletes adapt to various exercise intensities. However, the specific effects of combining Small-Sided Game (SSG) and Speed-Endurance Training (SET) on these parameters require the search for more effective solutions. This study aims to determine the effect of combined SSG and SET on heart rate (HR) and rate of perceived exertion (RPE). Material and Methods. This quantitative research employed an experimental method with a weekly pretest-posttest design. The study population consisted of eighty-two members of the Unesa Soccer Student Activity Unit. A sample of eighteen individuals was selected through simple random sampling. The sample had the following characteristics: age 20±0.69 years, weight 65±9.54 kg, height 165.22±4.31 cm, and BMI 22.82±1.92. Data were collected using the Polar H-10 device, and RPE interviews were conducted ten minutes after each training session. Data analysis was performed using paired sample t-tests and Wilcoxon tests. Results. The results showed a significant difference in HR for pair 1 (p = 0.037), but no significant differences for pair 2 (p = 0.058) or pair 3 (p = 0.076). However, the results for RPE indicated significant differences in pair 1 (p = 0.001), pair 2 (p = 0.004), and pair 3 (p = 0.002). The combination of SSG and SET led to an increase in HR during the first and second weeks. In the third week, HR decreased. RPE increased from the first to the second week. It then stabilized in the third and fourth weeks, indicating a consistent level of effort. The decrease in HR during the third week, despite the same effort level, suggests that the athletes successfully adapted to the training program. Conclusions. The combination of SSG and SET demonstrates potential as an effective training method for improving both physiological performance and adaptation in athletes. These findings offer valuable insights into how athletes respond to structured training programs, providing a foundation for future research and practical applications in sports training. The results contribute to a deeper understanding of the role that specific training combinations play in athlete development and recovery.